Natures urbaines - Yves Monnier (VertigO)
Trenelle in Fort-de France and La Mouzaïa in Paris are both strips of land springing up like “fragments” of countryside in the city and their style of housing personifies rustic life lost in time. Its inhabitants have inherited a shared history of the misery of displaced persons, crowding, social struggles and the foment of ideas. Even though Trenelle cultivates generally useful plants in their “Creole gardens” and La Mouzaïa gardens are construted for enjoyment. They both have a private quality and an amateurish practicality that differentiates them from parks, squares and other institutional green zones. Morever, these urban tracts preserve the authenticism of the relationship between man and nature and the biodiversity of these original green spaces is exceptional.